Anti-LGI1 antibody autoimmune encephalitis. Clinical case presentation and literature review - Stašaitytė , A.; Vanagas , T.; Danielius , V.; Jurkevičienė , G.; Balnytė , R. (Neurologijos seminarai, 2021)
Anti-leucine-rich glioma inactivated 1 (anti-LGI1) encephalitis is a rare autoimmune limbic encephalitis. As the clinical presentation of this disease is similar to other types of encephalitis most often associated with paraneoplastic process or endocrine disorder, a thorough testing for oncological or endocrine disease is necessary to correctly differentiate the diagnosis and administer appropriate treatment. We present a clinical case of a 63-year-old female patient treated in the Neurology Department of the Hospital of Lithuanian University of Health Sciences Kaunas Clinics for impairment of consciousness, probably of epileptic origin. After identifying memory problems, focal impaired awareness seizures, cognitive dysfunction, and typical brain magnetic resonance imaging changes, the diagnosis of limbic encephalitis was suspected. A thorough testing allowed to exclude paraneoplastic processes or endocrine syndromes, and the results of the cerebrospinal fluid antibody panel confirmed the diagnosis of anti-LGI1 antibody autoimmune encephalitis. Further treatment using glucocorticoids and intravenous immunoglobulin gave good results.